Cytomorphological Spectrum of Hashimoto's Thyroiditis and Its Correlation with Hormonal Profile and Hematological Parameters - Shetty, Archana (J Cytol, 2019)
INTRODUCTION: Hashimoto's thyroiditis (HT) is a well-known autoimmune disorder of the thyroid diagnosed on fine needle aspiration cytology (FNAC) and a common cause of hypothyroidism in women. Often serological and hematological parameters are additional investigations aiding the diagnosis of this entity. AIM: To grade HT based on cytomorphology and to correlate the cytological grades with thyroid hormone status and basic hematological parameters. MATERIALS AND METHODS: During a period of 2.5 years, 1762 patients underwent FNAC of thyroid at our tertiary healthcare center. Cytological evidence of lymphocytic thyroiditis was seen in 102 cases, of which 58 cases in addition had thyroid hormone levels and hematological parameters for correlation. RESULTS: Of the 58 cases, 55 were females. Majority of the patients had grade II thyroiditis (56.9%), followed by grade I (34.5%) and grade III (8.6%). Elevated thyroid-stimulating hormone was seen in 74.2% of cases, with 39.7% of patients presenting with subclinical hypothyroidism and 18.9% being euthyroid. Mean hemoglobin was low in all grades, more so in hypothyroid state, while other hematological parameters were normal when correlated with grade and hormonal status without any significant P value. CONCLUSION: Cytomorphological grading of HT can explain the pathogenesis of this autoimmune disease. Subclinical hypothyroidism was significantly observed. There was no significant statistical correlation of cytological grades with thyroid status. In this study, most of the hypothyroid cases had low hemoglobin levels while other basic hematological parameters did not show any statistically significant correlation with the thyroid hormonal status.